2018
DOI: 10.1002/ece3.4438
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of camera traps for quantifying daytime and nighttime visitation by vertebrate pollinators

Abstract: Identification of pollen vectors is a fundamental objective of pollination biology. The foraging and social behavior of these pollinators has profound effects on plant mating, making quantification of their behavior critical for understanding the ecological and evolutionary consequences of different pollinators for the plants they visit. However, accurate quantification of visitation may be problematic, especially for shy animals and/or when the temporal and spatial scale of observation desired is large. Sophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 45 publications
2
25
1
Order By: Relevance
“…2) suggested some differences in the efficiency of two popular camera models, but given that some studies (e.g. Krauss et al ., 2018) have identified the possibility of variation in performance of individual cameras from the same manufacturer, greater replication of individual cameras would be required to confirm whether the poor performance of the Moultrie camera for detecting rodents at 2 m is an intrinsic feature of this particular camera model. In this study, we found no statistically significant differences in performance among the individual Bushnell cameras used in the experiments (see Materials and methods).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2) suggested some differences in the efficiency of two popular camera models, but given that some studies (e.g. Krauss et al ., 2018) have identified the possibility of variation in performance of individual cameras from the same manufacturer, greater replication of individual cameras would be required to confirm whether the poor performance of the Moultrie camera for detecting rodents at 2 m is an intrinsic feature of this particular camera model. In this study, we found no statistically significant differences in performance among the individual Bushnell cameras used in the experiments (see Materials and methods).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are serious limitations on the ability of humans to make direct sightings. Humans lack visual acuity and the stamina needed for long observation periods, particularly at night (Steen, 2012; Krauss et al ., 2018). In addition, human presence can alter natural animal behaviour or deter animals from an area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the times when there are flowers in abundance, there can be nectar in excess of what the users can consume, but at other times, competition over limited nectar sources usually prevails. The potential competitors for honeybees include other types of honeybees, bumble bees, insects such as butterflies, bird species such as hummingbirds, and mammals like bats [39][40][41].…”
Section: Governance Issues Around Urban Beekeepingmentioning
confidence: 99%